2006
DOI: 10.1111/j.0021-9029.2006.00027.x
|View full text |Cite
|
Sign up to set email alerts
|

Geodemographic Differences in Knowledge About the Restaurant Tipping Norm

Abstract: A national telephone survey indicated that knowledge about the restaurant tipping norm is greater among people who are White, in their 40 s to 60 s, highly educated, wealthy, living in metropolitan areas, and living in the Northeast than among their counterparts. These findings support the idea that differential familiarity with tipping norms underlies geodemographic differences in tipping behavior. An educational campaign promoting the 15-20% restaurant tipping norm is needed to reduce geodemographic differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

5
24
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 23 publications
5
24
1
Order By: Relevance
“…Both motives may be weaker among blacks than among whites. Blacks are less likely than whites to know the norm (Lynn 2004b(Lynn , 2006 and, thus, are less able to pass it on to their children or friends. As a consequence, blacks are probably more likely to learn tipping norms from strangers.…”
mentioning
confidence: 99%
“…Both motives may be weaker among blacks than among whites. Blacks are less likely than whites to know the norm (Lynn 2004b(Lynn , 2006 and, thus, are less able to pass it on to their children or friends. As a consequence, blacks are probably more likely to learn tipping norms from strangers.…”
mentioning
confidence: 99%
“… Lynn (2004a, 2006a; Lynn & Thomas‐Haysbert, 2003) has conducted studies that have explored differences between populations with respect to tipping. …”
mentioning
confidence: 99%
“…For example, previous research has found that Blacks in the United States tip less than Whites in large part because they have different perceptions and beliefs about the customary or normative tip amount (Lynn, 2004(Lynn, , 2006b(Lynn, , 2011. In fact, approximately 70 percent of White adults in the U.S. believe that it is customary or normative to tip 15-20 percent of the bill size in restaurants while only about 35 percent of Black adults in the U.S. hold this belief (Lynn, 2004(Lynn, , 2006b.…”
mentioning
confidence: 99%
“…Researchers have convincingly demonstrated that SES is only a weak and partial mediator of race differences in beliefs about tipping norms (Lynn, 2004(Lynn, , 2006b), but no one has examined if and how SES might interact with race to affect beliefs about tipping norms. This gap in the literature deserves investigation because a long standing theory is that the more middle-class or bourgeois Blacks are, the weaker their ethnic or race commitment (Frazier, 1957).…”
mentioning
confidence: 99%
See 1 more Smart Citation